Aplicação de trinexapaque etílico na fase reprodutiva do trigo para manejo da germinação pré-colheita - Tonatto, Matheus (2017)
The objective of this study was to identify the existence of an inhibitory effect of the chemical compound Trinexapac-ethyl on wheat pre-harvest sprouting. Two experiments were carried out in greenhouse conditions in the years of 2015 and 2016, using a randomized complete block design with three replications. In the first one, different doses of Trinexapac-ethyl (0; 50; 100; 200; and 400 g of active ingredient ha-¹) were applied at three phenological stages (Z77, Z83 and Z91), in Taurum cultivar, to identify the most responsive stage to apply the product. In the second one, the same doses were applied to cultivars BRS 207, Jadeíte 11, TBIO Iguaçu, TBIO Tibagi, TEC Vigore, Taurum, Frontana and TEC Veloce, which present different levels of susceptibility to pre-harvest sprouting. Phenotyping was performed in a germination chamber by collecting and threshing the seeds of eight spikes per replicate. We identified the Z77 stage as the most responsive to the application of Trinexapac-ethyl. We observed a decreasing linear behavior in the germination with the increase of the applied doses for the cultivars, except for Frontana. The use of Trinexapac-ethyl, at a dose of 400 g of active ingredient ha-¹ and applied at the Z77 stage, reduces pre-harvest sprouting by up to 82%.